2018
DOI: 10.1007/s40273-018-0614-9
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Preferences in Germany Differ Among Apheresis Patients with Severe Hypercholesterolemia

Abstract: Regarding patient preference, clinical efficacy seems to dominate. Hence, 'reduction of LDC-C in blood' was ranked highest above patient-relevant modes of administration and adverse effects. In the patient groups identified, reduction of apheresis was important for only a subsegment (30%) of patients. Another 30% wanted effective LDL-C reduction by whatever means necessary. Most strikingly, another 30% preferred higher frequencies of apheresis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Stated preferences methods such as discrete choice experiments (DCE) and BWS are widely used in healthcare and increasingly discussed by regulators. [16][17][18][19][20][21] They are based on the assumption that health products or services can be described in terms of their characteristics (attributes and levels). Participants are repeatedly asked to choose between 2 or more alternatives, such as healthcare products, drugs, or services, in differing-choice scenarios simulating real choice decisions.…”
Section: Best-worst Scaling Casementioning
confidence: 99%
“…Stated preferences methods such as discrete choice experiments (DCE) and BWS are widely used in healthcare and increasingly discussed by regulators. [16][17][18][19][20][21] They are based on the assumption that health products or services can be described in terms of their characteristics (attributes and levels). Participants are repeatedly asked to choose between 2 or more alternatives, such as healthcare products, drugs, or services, in differing-choice scenarios simulating real choice decisions.…”
Section: Best-worst Scaling Casementioning
confidence: 99%
“…A previous study conducted in Germany on therapy preferences for lipid‐lowering drugs highlighted the significance of the attributes ‘reduction of LDL‐C level’, ‘risk of myopathy’ and ‘frequency of apheresis’ among patients with severe hypercholesterolaemia. 19 However, since lipoprotein apheresis is infrequently used in China, our study did not include ‘frequency of apheresis’ as an attribute. Considering the high occurrence of liver damage as an adverse drug reaction in the Chinese population, 27 we included ‘risk of liver damage’ as an attribute.…”
Section: Discussionmentioning
confidence: 99%
“… 14 These preference evidence can inform clinical decision‐making and facilitate shared decision‐making, ultimately leading to improved healthcare outcomes. However, the literature review has identified only one study that explored patient preferences for lipid‐lowering drugs using DCE, 19 and it did not include out‐of‐pocket cost as an attribute since the German healthcare system does not rely on co‐payments. Conversely, out‐of‐pocket cost was a key factor influencing treatment decisions in China.…”
Section: Introductionmentioning
confidence: 99%
“…Again, we applied effect coding on all variables except for age. As recommended for analyses with a small sample size (< 300) as well with the intention to provide a probable allocation of the participants per group, we examined AIC, BIC, and sample-size adjusted BIC to select the best-fitting model [ 40 42 ]. The information criteria led to heterogenous recommendations (ESM).…”
Section: Methodsmentioning
confidence: 99%